The major Al Medinat fault; an Atlasic reworking of a complex Variscan shear zones system (western High Atlas, Morocco) - Dias, Rui (2017)
The geological pattern of Morocco is the result of a strong interference between several orogenic cycles from the Precambrian to recent times, which led to the individualization of different tectonic domains. Their boundaries are mostly the result of brittle deformation, induced by the Cainozoic compressive tectonic setting between Eurasia and African plates. This gives rise to wide plains of sub-horizontal Cainozoic sedimentary sequences (e.g. Haouz and Sousse plains), bounded by elevated blocks. In such blocks a much more complex structure is found: - The Precambrian and Palaeozoic sequences has been deeply deformed during Pre-Mesozoic orogens, mainly in a pervasive way by the Variscan collision between Gondwana and the northern peri-Gondwana Terranes; - Unconformably overlying the older rocks, the Meso-Cainozoic usually presents a weak alpine deformation, except in the vicinity of the faults which has been active during the atlasic inversion. The influence of previous structures in the control of the alpine reworking of these Atlasic faults, is not always easy to understand. The Al Medinat fault system is one of the major structures of the western High Atlas, individualising a northern block, where the Meso-Cenozoic is preserved, from a southern uplifted one where some variscan intrusions (e.g. Tichka massif) outcrops. With a general E-W trend, its wavy pattern with frequent WNW-ESE and ENE-WSW segments, suggests a complex evolution, confirmed by detailed structures studies. The Variscan deformation in its vicinity, is marked by the strong deflection of the pervasive fabrics produced in the early stages of the major deformation phase (D1a); the regional NE-SW trend changes to WNW-ESE in relation with ductile shear zones (the Addouz, Adassil an Anamrou ones). These WNW-ESE sinistral shear zones, that have been used as pathways for sin-kinematic intrusions, should be ascribed to a late D1b stage (Dias et al, 2011). Previous structures have been offset a D2 Late-Variscan deformation along NNE-SSW to NE-SW brittle-ductile sinistral shear zones. Both previous D1b and D2 Variscan shear zones have been reworked by the Atlasic deformation with a major reverse sense movement giving rise to the general complex E-W trend of the Al Medinat fault sytem. The El Medinat model could be extrapolated in a more regional way. The boundaries of some of the main Atlasic features, like the contact between the Haouz plain and the western High Atlas, could be re-interpreted.